Utilizing Eutrophication Assessment Directives From Transitional to Marine Systems in the Thames Estuary and Liverpool Bay, UK - Greenwood, Naomi; Devlin, Michelle J.; Best, Mike; Fronkova, Lenka; Graves, Carolyn A.; Milligan, Alex; Barry, Jon; van Leeuwen, Sonja M. (Frontiers in Marine Science, 2019)
The assessment of eutrophic conditions is a formal requirement of several European Directives. Typically, these eutrophication assessments use a set of primary indicators which include dissolved inorganic nutrients, chlorophyll, dissolved oxygen and secondary information which can include phytoplankton community data. Each directive is characterised by a different geographical or political boundary which defines the area under assessment. Several disparate sources of data from the Thames estuary and Liverpool Bay in the United Kingdom collected from different monitoring programs were combined to generate a fully integrated dataset. Data sources included remote sensing, ecosystem models, moorings, freshwater inputs, and traditional ship surveys. Different methods were explored for assigning ecologically relevant assessment areas including delineation of the assessment area based on salinity, extent of the river plume influence and ecohydrodynamic characteristics in addition to the traditional geographically defined typologies associated with the different directives. Individual eutrophication indicators were tested across these revised typologies and outcomes of the different metrics compared across the river to marine continuum for the two UK areas. There have been statistically significant decreasing trends in the loads of ammonium, nitrite and dissolved inorganic phosphorous between 1994 and 2016 to both the Thames estuary and Liverpool Bay study areas but no statistically significant trends in loads of nitrate or dissolved inorganic nitrogen. There have been statistically significant increases in riverine nitrogen:phosphorous between 1994 and 2016. Nutrient concentrations exceeded assessment thresholds across nearly all areas other than the large offshore assessment areas and outcomes of the chlorophyll metric were often below assessment thresholds in the estuarine based areas and the offshore areas, but exceedances of thresholds occurred in the near coastal areas. However, trait-based indicators of phytoplankton community using functional groups show changes in plankton community structure over the assessment period indicating that additional metrics which quantify community shifts would be a useful measurement to include in future eutrophication assessments.